Network Reconfiguration Based on an Edge-Cloud-Coordinate Framework and Load Forecasting - Ning, Li; Si, Li; Nian, Liu; Fei, Zhong (Frontiers in Energy Research, 2021)
With the development of distributed energy resources (DERs), the power flow (PF) in distribution network (DN) is changed from unidirectional to bidirectional, resulting in complex control and coordinate measures. Network reconfiguration (NR) is a feasible solution for power gird side to deal with the complex PF. This paper proposed an edge-cloud coordinated reconfiguration framework with edge servers (ES) in the prosumers side and cloud servers (CS) in utility grid side, where the edge computing (EC) technology are implemented in ES to provide load forecasting (LF), while the cloud computing (CC) is used in CS to reconstruct the DN. The LF is implemented by the long-short term memory (LSTM) network to acquire the load information in advance, and the social preference of prosumers has been suggested for ES. The NR is formulated as a complex combinatorial optimization problem with the goal of minimizing power losses and solved by the advanced harmony search algorithm. Numerical results show the accuracy of LF and demonstrates the effectiveness of the proposed framework in terms of the NR power losses reduction.